Impact of Adjuvant Chemotherapy on FIGO Stage I Ovarian Clear Cell Carcinoma: A Systematic Review and Meta-Analysis - Yin, Min; Yang, Jiaxin; Zhou, Huimei; Liu, Qian; Li, Sijian; Zhang, Xinyue (Frontiers in Oncology, 2022)
Background Ovarian clear cell carcinoma (OCCC) is an uncommon subtype of epithelial ovarian carcinoma (EOC) that is often diagnosed at an earlier stage in younger women. It remains uncertain whether adjuvant chemotherapy improves the prognosis of patients with stage I OCCC. Objective This systematic review and meta-analysis aimed to assess the impact of adjuvant chemotherapy on survival in patients with stage I OCCC. Search Strategy Eligible studies were screened from PubMed, Web of Science, Embase, and the Cochrane Library up to October 10, 2021. Selection Criteria Studies that compared the oncological outcomes of adjuvant chemotherapy with observation were included. Data Collection and Analysis Six studies comprising a total of 4553 patients were enrolled in our study, of whom 3320 (72.9%) patients had undergone adjuvant chemotherapy and 1233 (27.1%) had not. Main Results The 5-year disease-free survival (DFS) and 5-year overall survival (OS) of stage I OCCC were 82.7% and 86.3%, respectively. In the overall population, adjuvant chemotherapy did not improve the 5-year DFS (83.2% vs 83.7%, OR 0.77, 95% CI 0.21-2.82, P=0.69) or 5-year OS (87.3% vs 83.6%, OR 1.30, 95% CI 0.86–1.98, P=0.22). Further subgroup analysis on stage IA/IB suggested that adjuvant chemotherapy did not impact 5-year DFS (OR 0.20, 95% CI 0.01-5.29, P=0.34) or 5-year OS (OR 1.52, 95% CI 0.78-2.98, P=0.22). For stage IC including 1798 patients, adjuvant chemotherapy revealed a significant survival benefit for 5-year OS (84.5% vs 83.3%, OR 1.44, 95% CI 1.08-1.94, P=0.01). Furthermore, the administration of adjuvant chemotherapy was found to be associated with a better 5-year OS (OR 4.98, 95% CI 1.12-22.22, P=0.04) in stage IC2/3. But no inferences regarding the effect of AC on stage IC2/3 can be made due to the limited size of the non-AC arm. Conclusion This study indicated that adjuvant chemotherapy did not improve the prognosis of stage IA and IB OCCC patients. However, for patients with stage IC, due to the retrospective, heterogenous and older data with limited sample size, the pooled results of our study should be interpreted with caution. More prospective studies on the role of adjuvant chemotherapy in stage I OCCC are warranted. Systematic Review Registration PROSPERO, CRD42021287749.